2005
DOI: 10.1029/2004tc001652
|View full text |Cite
|
Sign up to set email alerts
|

Relict Proterozoic basement in the Nanling Mountains (SE China) and its tectonothermal overprinting

Abstract: The basement beneath the Caledonian belt in SE China has been overprinted by Indosinian and Yanshanian events and is poorly known. In situ U‐Pb and Hf‐isotope analysis of zircons from granites and surrounding rocks in the Nanling Mountains area of the fold belt reveal that the Lanhe felsic gneiss is an outcrop of Mesoproterozoic basement, probably with a partly Late Archean protolith. This is consistent with Nd model ages of granites in this region, and exposures of Cathaysia basement in the coastal area of SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 51 publications
(84 reference statements)
3
87
0
Order By: Relevance
“…The metavolcanic samples of the Wanquan and Mamianshan Groups gave the SHRIMP zircon U-Pb ages of 728-826 Ma (Li WX et al, 2005;Wan et al, 2007;Li ZX et al, 2010). Amphibolite interlayers in the Chencai Group are dated at 832±23 Ma (in this study) Li, 1997;Xiang et al, 2008;Yu et al, 2009;Li XH et al, 1998;Li LM et al, 2011 ;Xu et al, 2005;Yu et al, 2006Yu et al, , 2007Yu et al, , 2009Yu et al, , 2010Wan et al, 2007Wan et al, , 2010Li ZX et al, 2010;Wang et al, , 2011Li WX et al, 2005 ;Li WX et al, 2005;Charvet et al, 2010; this study…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metavolcanic samples of the Wanquan and Mamianshan Groups gave the SHRIMP zircon U-Pb ages of 728-826 Ma (Li WX et al, 2005;Wan et al, 2007;Li ZX et al, 2010). Amphibolite interlayers in the Chencai Group are dated at 832±23 Ma (in this study) Li, 1997;Xiang et al, 2008;Yu et al, 2009;Li XH et al, 1998;Li LM et al, 2011 ;Xu et al, 2005;Yu et al, 2006Yu et al, , 2007Yu et al, , 2009Yu et al, , 2010Wan et al, 2007Wan et al, , 2010Li ZX et al, 2010;Wang et al, , 2011Li WX et al, 2005 ;Li WX et al, 2005;Charvet et al, 2010; this study…”
Section: Methodsmentioning
confidence: 99%
“…U-Pb analyses for five samples were carried out at the Institute of Geology and Geophysics, the CAS, using a Laser ICP-MS connected to a 193 nm excimer laser ablation system. The instrumental setting and detailed analytical procedure have been described by Wu et al (2006) (Li, 1997) and detrital zircons of 3.6-2.5 Ga (Xu et al, 2005;Yu et al, 2006) that was strongly reworked at ca. 446-425 Ma (e.g., Wan et al, 2007;Charvet et al, 2010;Wang et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 7. Frequency pattern of detrital zircon U-Pb ages for the sedimentary rocks from the Cathaysia (data are from Li et al, 2012;Yu et al, 2010;Wan et al, 2010Wan et al, , 2007Wang G S et al, 2009;Wang Y J et al, 2007;Yan et al, 2006;Xu et al, 2005) and Yangtze Block (data are from Duan et al, 2011;Yan et al, 2011;Li R B et al, 2010;Li X H et al, 2009Li X H et al, , 2008She, 2007;Zhang et al, 2006;Zheng et al, 2006), Tethyan-Himalaya (data are from Li et al, 2015;Usuki et al, 2013;Wang et al, 2013;Dong et al, 2011;Zhu et al, 2011;Myrow et al, 2010;McQuarrie et al, 2008;Gehrels et al, 2003) and Ailaoshan tectonic zone (data are from Nie, 2015 andWang et al, 2014), along with Wuliangshan Group (this study).…”
Section: Provenance and Tectonic Implicationsmentioning
confidence: 99%
“…In order to better evaluate the provenance of the Wuliangshan Group, it is statistically synthesized for the reported detrital zircon U-Pb ages for Late Paleozoic sedimentary rocks from the Yangtze, Cathaysia Block and the Ailaoshan and Tethys-Himalayan tectonic zones (Li D P et al, 2015;Nie, 2015;Wang Q F et al, 2014;Usuki et al, 2013;Wang Y J et al, 2013Wang Y J et al, , 2007Li X H et al, 2012Li X H et al, , 2009Li X H et al, , 2008Dong et al, 2011;Duan et al, 2011;Yan Y et al, 2011;Zhu et al, 2011;Li R B et al, 2010;Myrow et al, 2010;Yu et al, 2010;Wan et al, 2010Wan et al, , 2007Wang G S et al, 2009;McQuarrie et al, 2008;She, 2007;Yan D P et al, 2006;Zhang et al, 2006;Zheng et al, 2006;Xu et al, 2005;Gehrels et al, 2003), as shown in Fig. 7.…”
Section: Provenance and Tectonic Implicationsmentioning
confidence: 99%
“…With respect to the Precambrian metamorphic basement rocks distributed in western Cathaysia, such as Longchuan gneiss in northeast of Guangdong, Lanhe gneiss and Tanxi gneiss in northern Guangdong, Zengcheng gneiss in central Guangdong, and Xunwu gneiss in southern Jiangxi, their protoliths are all Neoproterozoic sedimentary rocks (Xu et al, 2005;Yu et al, 2006Yu et al, , 2007. As for the granulitefacies metamorphic rocks distributed in southwestern Fujian Province and the Yunkai areas which may represent lower crustal component are all parametamorphites, their protoliths are also Neoproterozoic sedimentary rocks (Yu et al, 2006).…”
Section: )mentioning
confidence: 99%